Exploration of the Art of Rodat Dance: How Social Education and Character Education Collaborate with Cultural Students? - Bagus Megiyono; Nassereddinali Taghavian; Spencer Empading Sanggin (Journal of Social Knowledge Education (JSKE), 2024)
Purpose of the study: The purpose of this research is to determine the form of revitalization carried out by the Sumber community in maintaining and developing local culture in Sumber Village, as well as to determine the form of social capital as a form of encouragement for the community to revitalize local culture. Methodology: The research used in this research is qualitative with phenomenological methods. The populationthis research is all the Sumber Village community who are involved efforts to revitalize Rodat Dance. Data collection used this research interview sheets and documentation. Data analysis using content analysis, interviews and observation notes. Data collection carried out through in-depth interviews with community, dance artists, village government representatives. Main Findings: The results of the research are the revitalization process carried out by the Sumber community in reviving Rodat culture by forming new Rodat members, carrying out activities and discovering new characteristics of Rodat dance, introducing culture the younger generation, holding cultural festivals as first step revitalization. Efforts carry out local cultural revitalization activities in Sumber Village are seen based three basic elements of social capital, namely trust in preserving cultural heritage, building social networks to carry out cultural festival activities. Novelty/Originality of this study: The novelty of applying local wisdom in social education creates promising new paradigm in understanding and overcoming social problems. By integrating local wisdom into the social education curriculum, this approach emphasizes relevance and depth students' understanding of the social reality around them. This is not just about providing information about social issues, but also exploring and utilizing existing local knowledge.